Análise de uma rede oportunista no transporte público urbano e proposta de novos protocolos de roteamento adaptados - Herek, Thiago Alexandre (2018)
This dissertation presents a mobility model designed for the representation of all urban public transport in the city of Curitiba-PR. The model is built using real data and offers better conditions of evaluation of the capacity of the environment as a platform for the construction of a VDTN and for the improvement of routing protocols specific to this type of scenario. The work also presents and evaluates the Spray and Wait-Bus and Prophet-bus protocols, as modifications of the original Spray and Wait and Prophet protocols. The proposed protocols use the characteristics of the environment to make better use of the contacts, in order to improve metrics such as delivery rate, delay and overload. In the Prophet-Bus protocol, the mechanisms of updating and aging of the delivery predictability are changed, altering the behavior of these functions in the vehicles that have contact with the destination along its route, already in the protocol Spray-and-Wait-Bus, are added routing decisions, nonexistent in the original protocol, exploring in the same way the characteristics of urban public transportation. Results obtained with Simulator One, using a traffic model representing a fleet monitoring application, together with the mobility model and the proposed protocols, first present delivery rates of up to 100% in some configurations of the environment. This result demonstrates the feasibility of using the mobility of urban public transport vehicles in the city for the efficient transportation of information. The results also demonstrate that the proposed protocols are capable of presenting higher delivery rates and lower overhead in all conditions tested compared to the original protocols.